Identification of Potential Plants Producing Tannin-protein Complex for a-amylase as Botanical Pesticide - Asriyah Firdausi; Tri Agus Siswoyo; Soekadar Wiryadiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Research  on  the  development  of  botanical  pesticides  should  be developed  through  new  methods,  such  as  by  inhibiting the  activity  of  digestive enzymes  by  secondary  metabolites.  The  aim  of  this  study  was  to  identify some  of  potential  plants  as  a  source  of  tannin-protein  complexes  to  inhibitthe  activity  of  - amylase.  The  study  of  identification  of  potential  plants producing  the  active  ingredient  tannin-protein  complex  was  divided  into  three stages,  1)  identification  of  potential  plants  producing  tannin,  2)  isolation  of tannin-protein  complexes,  and  3)  in  vitro  test  of  tannin-protein  complexes effect  of  the  -amylase activity.  Some  of  the observed  plants  were  sidaguri  leaf (Sida rhombifolia), melinjo leaf (Gnetum gnemon), gamal leaf (Gliricidia sepium),lamtoro  leaf  (Leucaena  leucocephala) ,  betel  nut  (Areca  catechu) ,  and  crude gambier  (Uncaria  gambir) a s  a  source of  tannins  and  melinjo  seed was  used  asprotein  source.  Betel  nut  and  melinjo  seed  were  the  best  source  of  tannin-protein  complex,  tannin  content  1.77  mg  TAE/mL  with  antioxidant  activity  of  90%,the  ability  to  inhibit  the  activity  of  -amylase by  95%  with  IC 50  values  of 10 mg/mL.Key words: Tannin, protein, -amylase, botanical pesticides,Areca catechu, Gnetum gnemon.